2006
DOI: 10.1126/science.1130837
|View full text |Cite
|
Sign up to set email alerts
|

Dok-7 Mutations Underlie a Neuromuscular Junction Synaptopathy

Abstract: Congenital myasthenic syndromes (CMSs) are a group of inherited disorders of neuromuscular transmission characterized by fatigable muscle weakness. One major subgroup of patients shows a characteristic "limb girdle" pattern of muscle weakness, in which the muscles have small, simplified neuromuscular junctions but normal acetylcholine receptor and acetylcholinesterase function. We showed that recessive inheritance of mutations in Dok-7, which result in a defective structure of the neuromuscular junction, is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
215
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(235 citation statements)
references
References 17 publications
10
215
1
2
Order By: Relevance
“…During the same year, Beeson et al identified DOK7 mutations in 21 patients with a clinical diagnosis of CMS exhibiting a limb girdle phenotype. [13][14] Since then DOK7 mutations have been confirmed in a significant number of other series. 53-54-55-56-57 The pathophysiological repercussions of DOK7 mutations appear to arise from abnormal activation of MuSK signalling leading to an abnormally unstable and simplified neuromuscular junction affecting both pre and postsynaptic structures.…”
Section: Dok-7 Deficiencymentioning
confidence: 89%
See 2 more Smart Citations
“…During the same year, Beeson et al identified DOK7 mutations in 21 patients with a clinical diagnosis of CMS exhibiting a limb girdle phenotype. [13][14] Since then DOK7 mutations have been confirmed in a significant number of other series. 53-54-55-56-57 The pathophysiological repercussions of DOK7 mutations appear to arise from abnormal activation of MuSK signalling leading to an abnormally unstable and simplified neuromuscular junction affecting both pre and postsynaptic structures.…”
Section: Dok-7 Deficiencymentioning
confidence: 89%
“…The kinetic mutations fall into two categories according to whether they induce slow or fast channel syndromes [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Defects In Acetylcholine Receptor Subunitsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,13,15,[17][18][19][20][21] Although there are no double-blind, placebo-controlled clinical trials for CMS, several drugs have shown convincingly positive clinical effects.…”
Section: Drugs Used In the Therapy Of Cmsmentioning
confidence: 99%
“…In adult mammals and most other vertebrates, each motor endplate is normally innervated by a single motor axon terminal and in most muscle fibres this NMJ is constrained to less than 0.1% of the muscle fibre cell surface (Sanes and Lichtman, 1999;Beeson et al, 2006). The strength of synaptic transmission at each NMJ in a motor unit virtually guarantees that all the muscle fibres supplied by a motor neuron contract in response to every action potential conducted into its motor nerve terminals (Wood and Slater, 2001).…”
Section: Introductionmentioning
confidence: 99%